LCL IN A SINGLE CORONAL SLICE – A NOVEL SIGN FOR IDENTIFYING ACL DEFICIENT PATIENTS AND PREDICTING RISK OF FUTURE GRAFT FAILURE. Issue 7 (30th July 2021) - Mitchell, Brendon C.; Siow, Matthew Y.; Chambers, Henry G.; Pennock, Andrew T.; Parvaresh, Kevin; Edmonds, Eric W.
Background: The ACL deficient knee is predisposed to anterior translation and internal rotation of the tibia. Hypothesis/Purpose: To show that knee deformity in an ACL deficient knee will produce a more vertical orientation of the lateral collateral ligament (LCL), allowing for the entire length of the LCL to be visualized on a single coronal slice (coronal LCL sign) on MRI, and that this sign is indicative of a greater risk for graft failure after ACL reconstruction. Methods: Charts were retrospectively reviewed to create 3 separate cohorts: normal ACL and no pathology involving the collateral ligaments (control cohort), ACL reconstruction without evidence for graft rupture, and ACL reconstruction with graft failure. Tibial translation and femorotibial rotation were measured on MRI, and posterior tibial slope was measured on lateral knee radiographs. Imaging was reviewed for the presence of the coronal LCL sign. Results: Deficient ACL (n=153) compared with intact ACL (n=70) was associated with significantly greater displacement regarding anterior translation (5.8mm internal rotation vs 0.3mm external rotation, p<0.001, respectively) and internal rotation (5.2 degrees vs. -2.4 degrees, p<0.001, respectively). The coronal LCL sign was present in a greater percentage of ACL deficient patients than intact ACL controls (68.6% vs. 18.6%, p<0.001, respectively) and associated with greater anterior tibial translation (7.2mm vs. 0.2mm vs., p<0.001) and internal tibial rotation (7.5 degrees vs 2.4 degrees, p=0.074). Multivariate analysis revealed the coronal LCL sign was significantly associated with an ACL tear (OR 12.8, p<0.001). Of the 153 ACL deficient cohort, 114 had no graft failure patients and 39 experienced graft failure. Mean follow-up time was 3.5 years (2 – 9.4 years). Coronal LCL sign was associated with graft failure (p=0.013), with an odds ratio of 4.3 for graft failure (p=0.003). Comparison of pre- and post-ACL reconstruction MRI in the graft failure cohort demonstrated reduced internal rotation, p= 0.00, but no change in coronal LCL sign (p=0.922). Conclusion: Our study shows that the coronal LCL sign correlates with the presence of an ACL tear and functions as a surrogate for the extent of axial and sagittal deformity. Further, we show that tibia internal rotation and posterior slope are independent predictors of ACL graft failure in adolescents. Whereas, the value of internal rotation could be improved with ACL reconstruction, the presence of the coronal LCL sign persisted over time and was predictive of graft rupture (without the need to make measurements or memorize values of significant risk). Figure 1.2. Rendering of knee deformity in ACL deficiency and effect on MRI projection of the LCL